Roadmap for achieving net-zero emissions in global food systems by 2050 - Costa, Ciniro; Wollenberg, Eva Karoline; Benitez, Mauricio; Newman, Richard; Gardner, Nick; Bellone, Federico (Springer, 2022)
Food systems (FSs) emit ~ 20 GtCO2e/y (~ 35% of global greenhouse gas emissions). This level tends to raise given the expected increases in food demands, which may threaten global climate targets. Through a rapid assessment, evaluating 60+ scenarios based on existing low-emission and carbon sequestration practices, we estimate that intensifying FSs could reduce its emissions from 21.4 to − 2.0 GtCO2e/y and address increasing food demands without relying on carbon offsets (e.g., related to afforestation and reforestation programs). However, given historical trends and regional contexts, a more diverse portfolio of practices, including diet shifts and new-horizon technologies, will be needed to increase the feasibility of achieving net-zero FSs. One likely pathway consists of implementing practices that shift food production to the 30th-percentile of least emission-intensive FSs (~ 45% emissions reduction), sequester carbon at 50% of its potential (~ 5 GtCO2e/y) and adopt diet shifts and new-horizon technologies (~ 6 GtCO2e/y). For a successful transition to happen, the global FSs would, in the next decade (2020s), need to implement cost-effective mitigation practices and technologies, supported by improvements in countries’ governance and technical assistance, innovative financial mechanisms and research focused on making affordable technologies in the following two decades (2030–2050). This work provides options and a vision to guide global FSs to achieving net-zero by 2050.